2009
DOI: 10.7553/75-2-98
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical model to predict customer satisfaction in relation to service quality in selected university libraries in Sri Lanka

Abstract: University library administrators in Sri Lanka have begun to search for alternative ways to satisfy their clientele on the basis of service quality. This article aims at providing a theoretical model to facilitate the identification of service quality attributes and domains that may be used to predict customer satisfaction from a service quality perspective. The effectiveness of existing service quality models such as LibQUAL, SERVQUAL and SERVPREF have been questioned. In that regard, this study developed a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 74 publications
1
17
0
Order By: Relevance
“…This result is in line with the research result of Parasuraman et al that states empathy dimension as the dimension with the lowest priority [14]. Jayasundara et al, precisely this dimension has a fairly high support in Sri Lanka [6]. This can be understood that the organization from the view point that' willingness to care and provide personal attention to their customers is an integral part quality improvement.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This result is in line with the research result of Parasuraman et al that states empathy dimension as the dimension with the lowest priority [14]. Jayasundara et al, precisely this dimension has a fairly high support in Sri Lanka [6]. This can be understood that the organization from the view point that' willingness to care and provide personal attention to their customers is an integral part quality improvement.…”
Section: Discussionsupporting
confidence: 87%
“…The highest gap in this research is tangible dimension, although findings in [2] by Sukardi and Wardana indicate the highest gaps are found in content and process standard dimensions. Tangible dimension is very influential on the other dimensions because standard on school infrastructure and facilities is part of the policy for fixing and improving basic services and quality of education process, including in the field of library services [6]. Tangible dimension is the ability of company to show to external parties its existence, such as physical facilities, technology, and employee appearance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hotel Industry should strengthen aesthetic labor. As the current social environment is service-oriented, service quality is the key factor that influences the competitive advantage of an organization (Jayasundara et al, 2009). The present study has shown that the friendly and warm attitude of the service staff is beneficial to the enhancement of the service quality.…”
Section: Managerial Implications Limitations and Future Studies 1mentioning
confidence: 99%